FASILITAS OBJEK WISATA DALAM PENGEMBANGAN DESA WISATA : KASUS BONO DI KECAMATAN TALUK MERANTI KABUPATEN PELALAWAN - Rina, Sri Febda (Komunitas Manajemen Kompetitif, 2018)
The purpose of the research to get detail contribution of hotel and restaurant in developing Bono Village Tourism at Teluk Meranti Bono Pelalawan. The specific purpose is to study the availablity of hotel and restaurant, training and also socializationthat received by hotel and restaurant’s owner to develop Bono Village Tourism. In this study Hotel and Restaurant is viewed from social and culture’s side in Hospitality which has twelve (12) elements, and this research are limited to study only for two elements, hotel and restaurant. The data was gathering from fifty (50) people from communities arround the village by having a discussion with them in one from. The data collected by a diret interview, discussion forum by using questionnaire and also direct observation. The research variable is type of hotels, tarining and socialization given to the communities to develop Bono Village Tourism. The data analysist by using SWOT analysist. The result of the study is training and socialisation is given to the hotel and restourant by government and Community Forum to improve the quality development of hotel and restaurant.